Comunicação interna em uma universidade pública - Silva, Sara Marli Magalhães Belarmino da (2007)
One searched on the basis of to search the process of formal internal communication of the Federal University of the Ceará the necessity of if perfecting the net of internal communication of this Institution, aiming at to contribute for the efficiency of the given services the university community. Ahead of this context, the study it had as objective generality to investigate the effect and factors of the process of formal internal communication of the UFC, being focused different dimensions of its operational aspect, in the functioning of the services played by the technician-administrative employees. For in such a way a bibliographical research was become fullfilled documentary and. The theoretical bedding of the bibliographical research included the revision of the following topics: the Theory of the Comunicativa Action in the perspective of Habermas (1987); the comunicacionais processes and barriers relating them with the strategical management of human resources and its effect in the work process. Leaving of the formatting of the theoretical referencial the metodológicos procedures to the light of the teachings of the authors had been defined, Trivinos (1987); Gil (2002); Roesch (1999) and Cochran (1977). The study it was characterized how much to the objectives as descriptive research and exploratória, how much the boarding technique case study, the analysis of the results was of quantitative nature. The method to select the employees was the estratificada random sample, considering the employees of campi of the Pici and Benfica, whose instrument used for collection of data was a questionnaire. The results of the research disclose that the formal process of internal communication in the UFC needs to be readjusted and to be perfected. The respondents point as main comunicacionais barriers the absence of feedback and the lack of comunicativa ability. This fact impacta in the operationalization of the Institution, reflecting in the quality of the services, generating noises, imperfections in the internal flow of communication.